Религиозната слобода како sine qua non за демократско граѓанско општество - Донев, Дејан (Conrad-Adenauer-Stiftung, 2008)
The basic problem of the multiethnic and multi-religious countries in transition is the lack of proper ethical education not just as a tool for building new system of values as a response of the needs caused by the transitional changes, but as well as a base for creating that kind of social and political climate in which ethical values will impose themselves as a criterion for estimating the maturity of society to face the challenges of multi-religious and multi-cultural on the way to the real civil democratic open society based on respecting of any kind of freedom, especially religious freedoms. Insisting on ethical education is a result of conscience for necessity of changing ethics of usage of the politics as a tool for flattering, to satisfy the daily political need and changes. This points not only the necessity of higher level on ethical education, but also on the fact that we must start the dialogue which will bring us to accepting of universal ethical values, independently of religious context from which they may come, as they were international putted by Hans Küng. Without discovering the common ground of ethical values, in this context, the idea of necessity of respecting the religious rights and freedoms of the others is a dream without the chance to become the reality. That’s way its necessary the religious freedom to be understant as a basic precondition for building and creating the really democratic open society founded on the idea that freedom means to be prepared to self subjugating in interest of keeping respecting on the other.
Religious freedom as a ‘sine qua non’ for democratic civil society
Keywords: слобода, религија, етика, демократско општество